Implementation of Advance Organizer Learning Model Based on Numbered Heads Together (NHT) to Improve Learning Outcomes of Students in 11th Grade Science on Buffer at SMAN 2 Balaesang - Reskiani Reskiani; Supriadi Supriadi (Jurnal Akademika Kimia, 2020)
The topic of buffer has connections between concepts and some prerequisite materials that students should understand to be able to facilitate this material. The lack of mastery on the material will lower the learning outcomes. This study aimed to improve students’ learning outcomes on buffer through the implementation of advance organizer learning model based on numbered heads together (NHT). This study was one group pretest-posttest design. The sample of this study was students of 11th grade Science at SMAN 2 Balaesang consisting of class XI Science 1 as the experiment class 1 with 33 students and class XI Science 2 as the experiment class 2 with 32 students. The effectiveness of the implementation of advance organizer learning model NHT-based can be seen from the average N-gain value of the experimental classes. The average N-gain value of experimental class 1 was 0.69 included in the medium category. While the average N-gain value of experimental class 2 was 0.71 included in the high category. Data analysis showed that the average value of students learning scores was greater than 65, where for the experimental class 1 was 76.36 and the experimental class 2 was 76.71. The advance organizer learning model NHT-based improved learning outcomes of students in 11th grade Science on buffer at SMAN 2 Balaesang.